Perennial Rule of the Masses: Class, Sex, and Decline in Ape and Essence. Issue 1 (April 2017) - Showers, Zachary
Abstract : For Aldous Huxley, the two most distressing things about people unlike himself are their ignorance and their birthrates, both of which are threatening the intellectualism that Huxley most admires. Huxley's own definition of Englishness is tied to intellectual and racial snobbery; people of his own race, status, and level of intelligence count as "English, " and he believes they are rapidly being overwhelmed by people of inferior quality from Asia, the Americas and the former colonies. Huxley's dystopian novel Ape and Essence (1948) ostensibly satirizes runaway technology, religious fanaticism, and government control, but the nostalgic ideal of white English superiority is also very much evident. The novel focuses on Huxley's prediction of horrible consequences when an ascendant lower class gains control. Ape and Essence portrays a society that has lost that which Huxley believes the intellectual elite protects—culture, tradition, and intelligence—and he does not allow the idea that the masses have the ability to do anything but destroy and pervert. Nearly all of this predicted destruction is caused by simple overpopulation, at least in Huxley's view, and he fears that the culture wars are being won by the masses simply because they are massive .